Embryo development stage and the location of embryo zygotic in the seed of citrine - Ribeiro, Valtemir Gonçalvez; Pasqual, Moacir; Ramos, José Darlan; Bearzoti, Eduardo; Neto, Santos D' Angelo (Pesquisa Agropecuaria Brasileira, 1999)
Controlled hybridizations between 'Natal' orange variety (Citrus sinensis Osb.) and male parent Poncirus trifoliata (L.) Raf. were performed in order to study zygotic and nucellar embryos behaviour at 120, 130, 140 and 150 days. At very date the seeds were removed and the embryos excised to characterize: development stage (globular, cordiform, torpedo and cotyledonal); colour (with or without chlorophyll); and location in the seed (close to the micropyle or more internal in the seed). From these characteristics contingency tables were evaluated to test independency hypothesis through Fisher test and c2 (chi-square). Dependence relationships were observed between the following characteristics: stages of the embryo development with location in the seed; stages of the embryo development with the seedling nature (zygotic or nucellar); between the plant nature with embryo location in the seed. It was observed that the most of the zygotic embryos at globular and cordiform stages were located close to the micropyle in the seed, behaviour at 130 to 150 days after pollination.